VARFARIN DOSE REGIME APPROACHS BASED ON PHARMACOGENETICS TEST RESULTS: REAL POSSIBILITY TO OPTIMIZE THE PHARMACOTHERAPY - D. A. Sychev; I. M. Antonov; S. V. Zagrebin; N. A. Gasanov; V. G. Kukes (Столичная издательская компания, 2015)
Indirect anticoagulants effectively prevent thromboembolic complications in patients with high risk of their development. It was proven in multicenter controlled studies. However in spite of efficient laboratory control of anticoagulant effect with the international normalized ratio, treatment with drugs of this group deals with high risk of bleeding including fatal one. Latest decade studies showed that efficacy and safety of indirect anticoagulants significantly depend on genetic factors in the form of polymorphisms of genes of their biotransformation (CYP2C9) and molecule-targets (VKORC1). This created basis for usage of pharmacogenetics approach for individual choice of indirect anticoagulant dose regime. However to use this approach in clinical practice physician needs to have algorithms for choosing of indirect anticoagulant dose regime according to pharmocogenetics test results. Analysis of these existing algorithms, their advantages and disadvantages are described in the review.